El Consejo Nacional de la Magistratura - García Toma, Víctor (Pontificia Universidad Católica del Perú, 2016)
The article is related to an autonomous constitutional body responsible for the selection, appointment, ratification and dismissal of the judges and prosecutors. Strictly speaking, it exercises a political and administrative function. The first one is understood because, by the rule of the Constitution, it exercises power of institutionalized determination and directs its decisions in accordance with ideological and juridical principles and values provided in said text. The second one is meant to expose a unilateral declaration of will made in the name and representation of the State that produces individual legal effects, immediately.

El artículo trata de un órgano constitucional autónomo encargado de la selección, nombramiento, ratificación y destitución de los jueces y fiscales. En puridad, ejerce una función político-administrativa. La primera se entiende en razón a que, por mandato de la Constitución, ejerce potestad de determinación institucionalizada y orienta sus decisiones conforme a los principios y valores ideológicos y jurídicos previstos en dicho texto. La segunda s e e ntiende e n r azón a e xponer u na d eclaración u nilateral de voluntad realizada a nombre y representación del Estado que produce efectos jurídicos individuales en forma inmediata.
The National Council of the Magistracy
Keywords: The National Council Of The Magistracy; Cnm; Constitutional Law; Peru; Constitution; Consejo Nacional de la Magistratura; Cnm; Derecho Constitucional; Perú; Constitución; https://purl.org/pe-repo/ocde/ford#5.05.00